TINGKAT PENGETAHUAN TENTANG KESEHATAN GIGI DAN MULUT KADER POSYANDU DI WILAYAH KERJA PUSKESMAS ABIANSEMAL I KABUPATEN BADUNG TAHUN 2018 - Ida Ayu Made Bintang Rusmini; Sagung Agung Putri Dwiastuti; Ida Ayu Dewi Kumala Ratih; Regina Tedjasulaksana (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2020)
Posyandu cadre were volunteers that assist the running of health services in Posyandu activities, should have knowledge and skills about the maintenance of oral health, so as to provide information about oral health to the community through posyandu activities. The purpose of this study is to know the level of oral health knowledge of Posyanducadre in Health Centre Abiansemal I of Badung Regency in 2018. This Descriptive study used total population as much as 165 cadre. Based on the study that the 89,32 % of cadre with the excellent of knowledge criteria, 8,73% with good criteria and 1,94 % cadre with enough. Avaragelevel of kwowledge of posyanducadreis 90,14% with education level of elementary school is 1 person,junior high school level 19 person,senior high school level 72 person,diploma level 4 person and bachelor degree 7 person. The conclusions of this study are Posyandu cadre in healtcentreAbiansemal I most have